2011
DOI: 10.1155/2011/945189
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of GaN HEMT Small Signal Parameters

Abstract: This study presents the temperature dependence of small signal parameters of GaN/SiC HEMTs across the 0–150°C range. The changes with temperature for transconductance (), output impedance ( and ), feedback capacitance (), input capacitance (), and gate resistance () are measured. The variations with temperature are established for , , , , , and in the GaN technology. This information is useful for MMIC designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…R ds is an important parameter that directly influences power added efficiency (PAE) and output power (P out ). The increase in R ds with temperature reduces the decline of power efficiency and P out with temperature [19].…”
Section: Temperature-dependent Rf Characterizationmentioning
confidence: 99%
“…R ds is an important parameter that directly influences power added efficiency (PAE) and output power (P out ). The increase in R ds with temperature reduces the decline of power efficiency and P out with temperature [19].…”
Section: Temperature-dependent Rf Characterizationmentioning
confidence: 99%
“…The magnitude and the trend with temperature of the small signal parameters of the two investigated devices agree qualitatively but not quantitatively with the reported GaN‐on‐SiC HEMTs, which could be due to the discrepancy in device structure, geometry, and fabrication. By comparing the extracted values of P ( T 0 ) and β for the two investigated devices, it can be found that they are comparable as their geometries are similar and bias condition are the same.…”
Section: Resultsmentioning
confidence: 47%
“…Previous studies have reported the temperature influence on the small signal parameters of GaN‐on‐SiC HEMTs. Alim et al investigated the small signal parameters as well as their temperature‐dependent behavior of two different technologies, ie, GaAs pHEMT and GaN‐on‐SiC HEMT, and analyzed their differences.…”
Section: Introductionmentioning
confidence: 99%
“…48 The reduction in charge confinement with temperature is expected to increase the feedback capacitance C gd , which may in turn reduce the value of C gs. 49 The magnitude and the trend with temperature of the small signal parameters of the investigated device agree qualitatively but not quantitatively with the reported GaN-on-SiC HEMTs, [45][46][47][48][49] which could be due to the discrepancy in device structure, geometry, and fabrication. Moreover, the comparisons of simulated and measured S-parameters of the 4 × 50 μm device at five different ambient temperatures are shown in Figure 16.…”
Section: Resultsmentioning
confidence: 54%